Indikasi CT Scan pada Tata Laksana Trauma Kepala pada Anak: Tinjauan Pustaka - Agus, Aurelia Michelle Calista (Cermin Dunia Kedokteran, 2026)
Head injury is an emergency case, including in the pediatric population. Pediatric head injury is a common cause of mortality and morbidity in the pediatric population. Head computed tomography (CT) scan is used as the gold standard in traumatic brain injury diagnosis, allowing for fast and accurate diagnosis. However, there are often constraints like limited facilities, uncooperative children, and risk of malignancy due to radiation exposure. Moreover, most pediatric head trauma cases are mild and only < 10% require neurosurgical intervention. Several algorithms and clinical decision protocols have been formulated to assist clinicians in determining the need for performing a CT scan, especially for children with minor head injury. The three most frequently used clinical decision rules are PECARN (Pediatric Emergency Care Applied Research Network), CATCH (Canadian Assessment of Tomography for Childhood Head Injury), and CHALICE (Children's Head Injury Algorithm for the Prediction of Important Clinical Events). Implementing these clinical decision rules may reduce unnecessary CT scans and minimize radiation exposure in children. Furthermore, these predictive algorithms can support faster, more effective, and safer clinical decision-making in the emergency management of pediatric head trauma.